A Comparative Study of Evaluation of Teaching Practice at B. Ed Level - Zhong Wanjuan,; Junaid, Muhammad; Shagufta Bibi,; Aafia Rasool (Corresponding Author), (Al-Qanṭara, 2024)
Teaching practice is important for the prospective teacher. It improves the teaching skill and ultimately the effectiveness of teaching and learning. The present study was carried under the title “A study of evaluation of teaching practice at B.Ed. level.” In order to match the world and be the part of future, Pakistan needs to focus on this issue. Teaching Practice in Pakistan has mostly been pressed with the notions of academic achievement, leaving less or no place for including teaching practice as a desired objective of education. The need is to raise for the teaching practice in teachers through teachers training and refresher courses. The objective of the study was to assess the effectiveness of teaching practice. A questionnaire was developed which was administer to a sample which comprised of 20 supervisors. The data was collected and analyzed by calculating %ages. The main conclusion was, majority of supervisor were of the opinion that teaching practice is necessary for trainee teachers. It is suggested that the study may be extended to the other campuses where classes for B.Ed. are held. The questionnaire may include factors helpful in analyzing the teaching practice. The number of trainee teacher’s assignment to each supervisor should be suitable.